In vitro antibacterial activity of Terminalia chebula leaf gall extracts against some human pathogenic strains - Shankara, BE Ravi; Ramachandra, YL; Rajan, S Sundara; Preetham, J; Ganapathy, PS Sujan (International Current Pharmaceutical Journal, 2012)
The leaf galls of Terminalia chebula is used widely as Karkatasringi in south Indian markets. Karkatashringi is an important crude drug employed in various indigenous systems of medicine against several diseases and the drug has diverse medicinal properties. The present study was carried out to understand the antimicrobial activity of various extracts. The antibacterial activity of T. chebula (leaf gall) was evaluated against ten bacterial strains including Gram-positive and Gram-negative bacteria using the agar-well diffusion method. Among the two extracts tested, the ethanol extract presented the best results against all the bacteria while aqueous extract showed moderate inhibition of the microbial growth. Each extract is unique against different microorganisms; Staphylococcus aureus was more susceptible to both extract among the tested organisms, whereas Serratia marcescens and Proteus mirabilis were less susceptible for ethanol and aqueous extract respectively. The inhibitory effect of the extracts was compared with standard antibiotic Ciprofloxacin. DOI: http://dx.doi.org/10.3329/icpj.v1i8.11254 International Current Pharmaceutical Journal 2012, 1(8): 217-220